Long Term Effects of Charge Redistribution in Cycled Bias Operating MOS Dosimeter - Sambuco Salomone, Lucas Ignacio (2016)
Techniques based on bias switching during the irradiation allow to extend the measurement range of MOS dosimeters. The response of the REM RFT300 RADFET dosimeter during bias cycled measurements shows a slow shift of the quasi-steady state threshold voltage value during radiation-induced charge neutralization. This phenomenon was previously explained as due to the presence of border traps. In this work, a recently developed numerical model which included the main physical processes leading to hole trapping and neutralization in MOS oxides was used to reproduce this experiment. The application of the model shows that the slow shift of the quasi-steady state threshold voltage during neutralization stages is a consequence of the spatial redistribution of trapped charge within the oxide. The effect this phenomenon has on MOS dosimetry is analyzed.